Obesity Determinants of Teenagers in Rural Areas (Universitas Negeri Semarang, 2020)
Obesity is excessive or abnormal fat deposits in adipose tissue, which will improve health. In 2015, at the age of 15 years, obesity was found to be 28.97%, and in Semarang District, it was found 54.56%. In 2017 obesity increased by â‰¥15 years, decreased by 6.04%. Whereas in Semarang Regency it was 6.68%. The percentage of the number that has increased, but the number of the number that has increased from the previous year. The aim of the study was to analyze the determinants of obesity in teenagers in rural areas. This study uses a case control design. The population consists of all high school/MA students in Semarang Regency. The sample consists of 35 obese and 35 non-obese teenagers, with the Purposive Sampling technique. The instruments used were Semi-Quantitative Food Frequency Questionnaire (SK-FFQ) and Physical Activity Questionnaire for Adolescent (PAQ-A). Data analysis using Chi-square test and logistic regression test. The analysis showed that there was a relationship between energy intake (p=0,000), protein intake (p=0.002), fat intake (p=0.008), carbohydrate intake (p=0.002), snack consumption (p=0.031), and physical activity (p=0.02) with obesity in teenagers in rural areas. The most dominant risk factors for obesity are energy intake, physical activity, and protein intake. Physical activity that can increase the risk of obesity in teenagers is decided to improve teenager welfare.